Edukasi Kesehatan Tentang Penanganan Anemia Pada Ibu Hamil Trimester III Sebagai Upaya Persiapan Persalinan Sehat - Yunika, Regina Pricilia; Yadul Ulya; Siskha Maya Herlina (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
Pregnancy causes the mother's body to experience various physiological changes that increase the need for nutrients. One of the most common nutritional problems during pregnancy is anemia. Anemia in pregnancy has negative impacts on the mother, fetus, and newborn. Therefore, it is important for pregnant women to understand how to prevent and treat anemia early through ongoing health education. Health education is a highly effective promotive and preventive effort to improve individual and group health knowledge, attitudes, and behaviors. The goal was to increase pregnant women's knowledge about anemia management in the third trimester as an effort to prepare for a healthy delivery. The methods used were counseling, discussion, question and answer sessions, and pre- and post-tests. There was an increase in pregnant women's knowledge, as evidenced by the number of pregnant women with good knowledge, increasing from 30% to 80% after receiving health education, a 50% increase. This increase indicates that the educational intervention provided was able to have a significant impact on increasing pregnant women's knowledge about anemia management in the third trimester as an effort to prepare for a healthy delivery